Numerical analysis of pulverized biomass combustion - Deniz Canal Cansu (EDP Sciences, 2021)
Combustion of pulverized biomass in a laboratory swirl burner is computationally investigated. The two-phase flow is modelled by an Eulerian-Lagrangian approach. The particle size distribution and turbulent particle dispersion are considered. The radiative heat transfer is modelled by the P1 method. For modelling turbulence, different RANS modelling approaches are applied. The pyrolysis of the solid fuel is modelled by a single step mechanism. For the combustion of the volatiles a two-step reaction mechanism is applied. The gas-phase conversion rate is modelled by the Eddy Dissipation Model, combined with kinetics control. The results are compared with measurements.